Changes in physicochemical properties of organic matter by uranium irradiation: A case study from the Ordos Basin in China. (January 2020) - Zhang, Fan; Jiao, Yangquan; Wu, Liqun; Rong, Hui; Zang, Bo
Abstract: Carbonaceous debris (CD) are exclusively disseminated in sandstones of uranium-bearing strata from the Dongsheng uranium ore field of the northern Ordos Basin, northern China. Physicochemical properties of CD were investigated through a series of tests including element analyses, Fourier transform infrared spectroscopy (i.e., FTIR) and organic carbon isotope (i.e., δC 13 ) as well as specific surface area. The results show that δC 13 of the samples from uranium-bearing strata range from −22.86‰ to −25.82‰, indicating that the CD is from the same origin. The average values of C, H, O and N are 54.54%, 4.55%, 39.15% and 0.49%, respectively, and H/C as well as O/C atomic ratios vary from 0.77 to 1.26 and 0.36 to 1.72, respectively, implying that CD is mostly composed of C and O, followed by H, and is grouped into Type Ⅲ kerogen at an immature to low mature stage. Compared with the samples without uranium enrichment, C, H, N and δ 13 C of the uranium-bearing samples increase by 13.66%, 5.32%, 12.50% and 0.98‰, respectively, while decrease by 18.50%, 7.84% and 33.33%, respectively, for O, H/C as well as O/C atomic ratios. As the intensity of uranium enrichment increases, H/C atomic ratios and aliphaticity decrease, and aromaticity increases. Besides, uranium-bearing samples are of smaller specific surface area than those without uranium enrichment. Alpha irradiation energy released by uranium and its daughters could cause the crosslinking in n -alkanes and long-chain polymers through a free-radical mechanism, which is supported by a decrease in O, aliphaticity and an increase in aromaticity. Hence, it results in polycondensation of molecular structure with a decrease in side chain length, function groups as well as specific surface area, and changes in physicochemical properties of organic matter, which is instructive in prospecting. Highlights: Uranium enrichment causes differences in element compositions of carbonaceous debris. Uranium-bearing carbonaceous debris is of a decrease of specific surface area by the influences of uranium enrichment. Aliphaticity and aromaticity decrease with the increased intensity of uranium enrichment.